EFFECTIVENESS OF IMPLEMENTATION OF PROBLEM BASED LEARNING MODELS TO IMPROVE STUDENTS’ MATHEMATICAL LEARNING OUTCOMES IN XI-MIPA SMA NEGERI 8 PEKANBARU - Restu Prabowo; Atma Murni; Zulkarnain (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2020)
The background of this research was the low ability of student’ mathematical learning outcomes of SMA Negeri 8 Pekanbaru. The purposes of this research were: 1) to find the significance of students’ mathematical learning outcomes who study through Problem Based Learning (PBL) model with student who study through conventional learning with scientific approach; (2) to examine the improvement of students’ mathematical learning outcomes who study through PBL model and students who study through conventional learning with scientific approach in class XI-MIPA SMA Negeri 8 Pekanbaru. This research was an experimental research (quasi experiment) with The Nonequivalent Pretest-Posttest Control Group Design. The population of this research is all students of class XI-MIPA SMA Negeri 8 Pekanbaru. Sample of this research consist of two classes, class XI-MIPA4 as experiment class and XI-MIPA3 as control class. The data of this research were student’s mathematical learning outcomes from pretest-posttest. Students’ mathematical learning outcomes were analyzed using independent sample t-test which was preceded by normality test and homogeneity of variances test. The result of this research shows that the improvement of students’ mathematical learning outcomes who study through PBL model is higher than students who study through conventional learning with scientific approach.